2021
DOI: 10.1097/qai.0000000000002727
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: No Difference in Urine Tenofovir Levels in Patients Living With HIV on Unboosted Versus Dose-Adjusted Boosted Tenofovir Alafenamide

Abstract: Background: Tenofovir alafenamide (TAF) is increasingly used in HIV treatment, with or without agents that require pharmacologic boosters such as ritonavir/cobicistat. Boosters increase TAF levels, so the TAF dose is lowered in single-pill combinations. We hypothesized that individuals on dose-adjusted boosted TAF would have similar urine tenofovir (TFV) concentrations to those on unboosted TAF.Setting/Methods: We collected urine samples from patients with HIV on TAF, with evidence of virologic suppression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Because self-reported ART adherence was high (with objective adherence metrics shown to be more reliable than self-report [9]), the availability of a POC tool to objectively measure adherence for patients on TFV-based regimens is useful. In settings in which frequent RNA monitoring is not feasible because of cost or access, POC testing could help clarify when virologic failures are more likely attributable to nonadherence (prompting interventions) or to resistance, requiring genotyping and potential ART change [9][10][11]. Even in settings in which frequent RNA checks are feasible, results are often not available in real time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because self-reported ART adherence was high (with objective adherence metrics shown to be more reliable than self-report [9]), the availability of a POC tool to objectively measure adherence for patients on TFV-based regimens is useful. In settings in which frequent RNA monitoring is not feasible because of cost or access, POC testing could help clarify when virologic failures are more likely attributable to nonadherence (prompting interventions) or to resistance, requiring genotyping and potential ART change [9][10][11]. Even in settings in which frequent RNA checks are feasible, results are often not available in real time.…”
Section: Discussionmentioning
confidence: 99%
“…To enrich our sample for individuals with adherence challenges, participants from POP-UP (a clinic serving patients with homelessness/unstable housing [8], embedded within 1 of our sites) received proactive outreach. Because we previously demonstrated that individuals have similar urine TFV concentrations on TAF whether dosed at 25 mg or 10 mg (with pharmacologic boosters) [9], we did not exclude participants based on TAF formulation. Urine TFV levels were measured by liquid chromatography tandem mass spectrometry at the University of California San Francisco (UCSF) using methods validated for urine [3,4].…”
Section: Methodsmentioning
confidence: 99%
“…TAF has equal efficacy with lower toxicity than TDF with lower dose (10-25 mg vs. 245 mg) [7]. The two TAF doses are related to its use in different combinations, such as with LPV/r (10 mg) or with DTG (25 mg), but do not influence the urine elimination of TAF that is similar with both doses [8].…”
mentioning
confidence: 99%